Protocol for a national cohort study to explore the long-term clinical and patient-reported outcomes and cost-effectiveness of implant-based and autologous breast reconstruction after mastectomy for breast cancer: the brighter study - Carmel Gulliver-Clarke; William Hollingworth; Shelley Potter; Paul White; Syed Mohiuddin; Patricia Fairbrother; Chris Holcombe; Ranjeet Jeevan; Leigh Johnson; Joe M O’Donoghue; Mairead MacKenzie (BMJ Open)
Introduction Breast reconstruction (BR) is offered to improve quality of life for women with breast cancer undergoing mastectomy. As most women will be long-term breast cancer survivors, high-quality information regarding the long-term outcomes of different BR procedures is essential to support informed decision-making. As different techniques vary considerably in cost, policymakers also require high-quality cost-effectiveness evidence to inform care. The Brighter study aims to explore the long-term clinical and patient-reported outcomes (PROs) of implant-based and autologous BR and use health economic modelling to compare the long-term cost-effectiveness of different reconstructive techniques.Methods and analysis Women undergoing mastectomy and/or BR following a diagnosis of breast cancer between 1 January 2008 and 31 March 2009 will be identified from hospital episode statistics (HES). Surviving women will be contacted and invited to complete validated PRO measures including the BREAST-Q, EQ-5D-5L and ICECAP-A, or opt out of having their data included in the HES analysis. Long-term clinical outcomes will be explored using HES data. The primary outcome will be rates of revisional surgery between implant-based and autologous procedures. Secondary outcomes will include rates of secondary reconstruction and reconstruction failure. The long-term PROs of implant-based and autologous reconstruction will be compared using BREAST-Q, EQ-5D-5L and ICECAP-A scores. Multivariable regression will be used to examine the relationship between long-term outcomes, patient comorbidities, sociodemographic and treatment factors. A Markov model will be developed using HES and PRO data and published literature to compare the relative long-term cost-effectiveness of implant-based and autologous BR.Ethics and dissemination The Brighter study has been approved by the South-West -Central Bristol Research Ethics Committee (20/SW/0020), and the Confidentiality Advisory Group (20/CAG/0021). Results will be published in peer-reviewed journals and presented at national meetings. We will work with the professional associations, charities and patient groups to disseminate the results.